Theory, revealing the content and the choice of methodology ethnic social-pedagogical monitoring studies: a comparative analysis of the countries of Europe. (Journal of Educational Sciences, 2016)
The article reveals the experience of Bulgaria in the implementation of inter cultural education. Bulgaria is a multiethnic country. So urgent is the problem of integration of ethnic minority children in the state education system, reduce risk children who are not enrolled in formal education. Article consists of the following sections:– Introduction;– Model inter cultural education as methodology of pedagogical researches of ethno-social monitoring;– International and European documents relating to the education of children and pupils from ethnic minorities;– Experience of Bulgaria;– Strategic goal of learning problems inter cultural education;– Conclusion. What are the criteria of quality of work of teachers in multicultural environment?The article will detail the theory liberalism, multiculturalism, inter cultural education. Analyzed European and Bulgarian documents of education. Describes the strategy and action plan of the state for the integration of children of ethnic minorities in Bulgarian society. Are the strategic objectives and expected results of the application of thestandard. One of the important directions of realization of strategy - pedagogical preparation and improvement of qualification of teachers on problems of inter cultural education. Criteria of quality of work of teachers in multicultural environments: personal professional criteria; the process of interaction with students; educational process; out-of school and extracurricular activities; educational interaction with other teaching subjects. Implementation inter cultural education allows to realize the right to education «for all children» taking into account state and European approaches, as well as taking into account the ethnic characteristics of the education of the individual.
Keywords: teacher; ethnic psychology; intercultural dialogue; intercultural education; multicultural environment; European documents of education